Layer selective magnetic moment distribution in an epitaxial double spin valve structure: Si(001)/Cu/FeNi/Cu/Co/Cu/FeNi/Cu - Samad, A; Choi, B; Langridge, S; Penfold, J; Bland, J (IEEE, 1999)
A study was carried out to determine selectively the magnetic moment configuration in an epitaxial double spin valve structure with nominal composition: Si(001)/Cu(700 angstrom)/FeNi(60 angstrom)/Cu(60 angstrom)/Co(40 angstrom)/Cu960 angstrom)/FeNi(60 angstrom)/Cu(50 angstrom). The conditions under which it is possible to control the relative alignment of the FeNi and Co layers were determined.